2009
DOI: 10.1128/iai.01310-08
|View full text |Cite
|
Sign up to set email alerts
|

Immune Evasion ofLeptospiraSpecies by Acquisition of Human Complement Regulator C4BP

Abstract: Leptospirosis is a spirochetal zoonotic disease of global distribution with a high incidence in tropical regions. In the last 15 years it has been recognized as an important emerging infectious disease due to the occurrence of large outbreaks in warm-climate countries and, occasionally, in temperate regions. Pathogenic leptospires efficiently colonize target organs after penetrating the host. Their invasiveness is attributed to the ability to multiply in blood, adhere to host cells, and penetrate into tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
84
0
26

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 44 publications
(51 reference statements)
2
84
0
26
Order By: Relevance
“…However, studies on the mechanisms underlying this resistance were only recently initiated. Acquisition of fluid-phase host complement regulators on the surfaces of pathogens is a common complement evasion mechanism, and it has been demonstrated that pathogenic Leptospira strains are able to bind factor H (FH), factor H-like 1 (FHL-1), factor H-related 1 (FHR-1), and C4b binding protein (C4BP) (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…However, studies on the mechanisms underlying this resistance were only recently initiated. Acquisition of fluid-phase host complement regulators on the surfaces of pathogens is a common complement evasion mechanism, and it has been demonstrated that pathogenic Leptospira strains are able to bind factor H (FH), factor H-like 1 (FHL-1), factor H-related 1 (FHR-1), and C4b binding protein (C4BP) (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Complemento, variando desde a ligação a proteínas reguladoras, como C4BP e FH (Barbosa et al, 2009;Castiblanco-Valencia et al, 2012;Meri et al, 2005;Silva et al, 2011), até a degradação de moléculas de C3 e seus fragmentos por enzimas secretadas no microambiente próximo às leptospiras (Fraga et al, 2014). Esses mecanismos de evasão podem explicar a maior capacidade de leptospiras patogênicas, como a LPF, em sobreviver no soro, enquanto espécies saprófitas, como a L. biflexa, são bastante sensíveis, sendo eliminadas após poucas horas de incubação (Barbosa et al, 2009;Meri et al, 2005) Ao contrário do que inicialmente esperávamos, a infecção das linhagens B6 C5 + e A/J C5 -com doses crescentes de LPF não acarretou em alterações significativas do número de leucócitos circulantes e nas concentrações de ALT e AST no soro e de citocinas pró e antiinflamatórias no fígado dos camundongos infectados.…”
Section: Discussionunclassified
“…Esses mecanismos de evasão podem explicar a maior capacidade de leptospiras patogênicas, como a LPF, em sobreviver no soro, enquanto espécies saprófitas, como a L. biflexa, são bastante sensíveis, sendo eliminadas após poucas horas de incubação (Barbosa et al, 2009;Meri et al, 2005) Ao contrário do que inicialmente esperávamos, a infecção das linhagens B6 C5 + e A/J C5 -com doses crescentes de LPF não acarretou em alterações significativas do número de leucócitos circulantes e nas concentrações de ALT e AST no soro e de citocinas pró e antiinflamatórias no fígado dos camundongos infectados. Ambas as linhagens foram capazes de controlar a infecção, tendo os animais infectados, independente da dose utilizada, um número de leucócitos na circulação periférica e níveis de ALT e AST no soro e de citocinas pró e antiinflamatórias no fígado semelhante ao observado nos animais dos grupos controle (PBS (Santos et al, 2010).…”
Section: Discussionunclassified
See 2 more Smart Citations